The architecture of the Catholic Church in the modern movement in Indonesia - Rosalia Rachma Rihadiani; Ikaputra (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Catholic church architecture is part of the development of architecture, especially in Europe. The rationalism and density of iconic Catholic church buildings in Europe raise the allegation that the architecture of the Catholic church during the modern movement was not found in Europe but appeared in missionary areas, including Indonesia. Queen Wilhelmina adopted the ethical policy in 1901 was a driving factor for the emergence of modern-style buildings in Indonesia, including the Catholic church building. Symbols and ornaments are part of the architecture of the Catholic Church; this is contrary to the anti-ornament school of modern architecture. This research looks at the architecture of the Catholic Church in Indonesia during the 1890 - 1945 period of the modern movement. The research method used descriptive qualitative with secondary data collection. The results showed that the architecture of the Catholic Church in Indonesia during the modern movement had an identity: geometric shapes on the facade, simple symbols and ornaments and a three-dimensional roof.